L-Histidinol Dehydrogenase as a New Target for Old Diseases - M. Monti, Simona; De Simone, Giuseppina; D128;™Ambrosio, Katia (Current Topics in Medicinal Chemistry, 2016)
Bacterial infections constitute an always growing health problem worldwide. The resistance to antibiotics of an increasing number of bacterial pathogens necessitates a permanent search for new molecules with different mechanisms of action. Histidine biosynthesis is an ancient pathway found in bacteria, archaebacteria, fungi and plants but absent in mammals. This feature makes it very interesting for the study of new strategies aimed to develop novel classes of antibacterial agents. In particular, one of the enzymes involved in the histidine biosynthesis, i.e. L-histidinol dehydrogenase (HDH), has been demonstrated to be essential for the survival of bacteria associated to several infections, such as brucellosis and tubercolosis. HDH is a Zn2+ enzyme which catalyzes the last two steps in the biosynthesis of Lhistidine: sequential NAD-dependent oxidations of L-histidinol to L-histidinaldehyde and then to L-histidine. This review will be focused on the biochemical and structural studies performed on HDH so far with the purpose to provide a structural background for the rational drug design of potent HDH inhibitors.
Keywords: L-histidinol dehydrogenase